2020
DOI: 10.3389/fendo.2020.00246
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Embryo Morphokinetics Are Not Affected by a Switch of the Ovarian Stimulation Protocol Between GnRH Agonist vs. Antagonist Regimens in Consecutive Cycles

Abstract: Background: The impact of controlled ovarian stimulation (COS) during medically assisted reproduction (MAR) on human embryogenesis is still unclear. Therefore, we investigated if early embryonic development is affected by the type of gonadotropin-releasing hormone (GnRH) analog used to prevent a premature LH surge. We compared embryo morphology and morphokinetics between GnRH agonist and antagonist cycles, both involving human chorionic gonadotropin (hCG)-trigger. To reduce possible confounding factors, we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Freis et al were able to show altered embryo morphokinetics in patients with endometriosis compared to non-endometriosis patients, resulting in poorer embryo quality [ 15 , 16 ]. Consistent with our data, they found that it was not the timing of the specific events during early embryo development, but the relative kinetics of the embryo development that changed between the two study groups, with a negative effect for the endometriosis group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Freis et al were able to show altered embryo morphokinetics in patients with endometriosis compared to non-endometriosis patients, resulting in poorer embryo quality [ 15 , 16 ]. Consistent with our data, they found that it was not the timing of the specific events during early embryo development, but the relative kinetics of the embryo development that changed between the two study groups, with a negative effect for the endometriosis group.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory peritoneal fluid shows a toxic effect on embryos [ 28 ]. This may affect morphokinetic timing, but there is only limited data on morphokinetics and endometriosis [ 15 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 107 ] No difference is noted in embryo morphokinetics within individuals undergoing IVF when switched between antagonist and agonist protocols. [ 108 ]…”
Section: T He E Fficacy Of S ...mentioning
confidence: 99%
“…Compared with the shorter learning curve period of the GnRH agonist protocol, that of the antagonist protocol was relatively longer. Numerous studies regarding antagonist protocols focused on the population to whom these protocols could be applied, the success rate of fresh embryo transfer, and the influence of hormone levels on pregnancy outcomes (6)(7)(8). However, only few studies have explored the flexible conversion of antagonist protocols.…”
Section: Introductionmentioning
confidence: 99%